Creating Environments Through the Art of Occupational Therapy - Lydia Royeen (Scholarworks @ WMU, 2016)
Dr. Lori Reynolds has an interest in therapeutic gardens and the creation of living spaces that promote wellbeing for older adults. Dr. Reynolds educates various stakeholders on the benefits of occupational therapy, including landscape architects and senior living administrators. Her advocacy to expand occupational therapy beyond its mainstream roles is infectious. She speaks passionately about her work in helping to create therapeutic gardens and how her role as an occupational therapist offers great perspective in this process. She appreciates the environmental impact on an individual's health and well-being and practices from a personenvironment-occupation theory